Constructive heuristic algorithm for the DC model in network transmission expansion planning - Romero, R.; Rocha, C.; Mantovani, JRS; Sanchez, I. G. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
A novel constructive heuristic algorithm to the network expansion planning problem is presented the basic idea comes from Garver's work applied to the transportation model, nevertheless the proposed algorithm is for the DC model. Tests results with most known systems in the literature are carried out to show the efficiency of the method.